Rules and Reasoning 6th International Joint Conference on Rules and Reasoning, RuleML+RR 2022, Berlin, Germany, September 26-28, 2022, Proceedings - Governatori, Guido; Turhan, Anni-Yasmin. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the proceedings of the International Joint Conference on Rules and Reasoning, RuleML+RR 2022, held in Berlin, Germany, during September 26-28, 2022. This is the 6th conference of a new series, joining the efforts of two existing conference series, namely "RuleML" (International Web Rule Symposium) and "RR" (Web Reasoning and Rule Systems). The 18 full research papers presented in this book were carefully reviewed and selected from 54 submissions. The papers cover the following topics: answer set programming; foundations of nonmonotonic reasoning; datalog; queries over ontologies; proofs, error-tolerance, and rules; as well as agents and argumentation.
Answer Set Programming -- Foundations of Nonmonotonic Reasoning -- Datalog -- Queries Over Ontologies -- Proofs, Error-tolerance, and Rules -- Agents and Argumentation.
Keywords: Computer science; Information technology-Management.; Database management; Logic programming; Expert systems (Computer science).; Natural language processing (Computer science).; Theory of Computation; Computer Application in Administrative Data Processing; Database Management; Logic in AI; Knowledge Based Systems; Natural Language Processing (NLP).